Grapevine virus T is relatively widespread in Slovakia and Czech Republic and genetically diverse - Glasa, Miroslav; Predajňa, Lukáš; Sihelská, Nina; Šoltys, Katarína; Ruiz-García, Ana Belén; Olmos, Antonio; Wetzel, Thierry; Sabanadzovic, Sead (Virus genes, 2018)
A recently described putative foveavirus, grapevine virus T (GVT), was detected in a Slovak grapevine accession (SK704) using high-throughput sequencing, prompting further studies. Full-length genome sequence of isolate GVT-SK704 was determined. Analyses revealed 86.1% nucleotide identity with the Italian GVT isolate, currently the only available nearly complete sequence of GVT in GenBank. A virus-specific RT-PCR assay was developed, which enabled a survey of GVT incidence in grapevine samples from Slovakia and Czech Republic. Unexpectedly, GVT was present in ~ 30% of tested samples. Analysis of complete CP gene sequences of 20 Slovak and Czech GVT isolates detected in the survey revealed relatively high intra-species variability (up to 11.2% nucleotide divergence), suggesting multiple introductions from different sources, possibly over an extended period of time.
Keywords: Genomics; Plant Diseases; Genome, Viral; Czech Republic; Slovakia; Česká republika; genom virový; Phylogeny; genomika; Genetic Variation; nemoci rostlin; fylogeneze; genetická variace; Slovenská republika; Flexiviridae